Оценка доступности образовательных ресурсов для лиц с ограниченными возможностями на основе существующих стандартов оценки качества программного обеспечения - Arapova, Elizabeth Aleksandrovna; Kramarov, Sergey Olegovich; Sakharova, Luydmila Victorovna; Tishchenko, Evgeniy Nikolaevich (Современные информационные технологии и ИТ-образование; Том 16 № 1 (2020): Современные информационные технологии и ИТ-образованиеDO - 10.25559/SITITO.16.202001.177-186, 2020)
The article provides a review of literary sources on the problems of evaluating the quality of software systems. The concept of accessibility is considered. Attributes that are most important for building an architecture Web-oriented educational systems Attributes are available based on the international standard WCAG 2.0-2.1 and are classified by types of psycho-physiological human disorders. This model is based on a three-level model of accessibility, which can be used to make an informed choice of the optimal resource in accordance with the individual needs of the student.